IMPORTANT FACTORS FOR BASKETBALL INITIATION (Fiep Bulletin - online, 2011)
Nowadays it is known to replace the machine man, realizing the reduction of body activity, but although, it increases the hours of leisure with interaction / interactivity through multimedia systems. So, raise the need for the practice of physical activities, recreation and sports. Such activities need to be targeted appropriately, be they individual or collective. Please be informed that there are correct age to be initiated, later being incorporated into everyday life of the individual. Therefore would be part of his adult life making him physically active. It is known that the benefits for growth, as well as for the human cardiovascular system are considerable, when performing physical activities. An individual practicing sports and physical exercise have better quality of sleep, rules of coexistence, in addition, social development, emotional and mental. Thus, epistemologically this article portrays the collective sports, specifically the case of basketball. Over the years as a professional in the area of Physical Education, defended the idea that for children from 07 to 10 years should be accorded various activities with myriad movements, providing formidable motor experiences through various moves, that even before being initiated to team sports (MEC). It is believed that this must happen not only to teach basketball, but in any sport collective. We know the importance of coordinative aspects to the practice of the MEC, especially basketball, which in their actions during the game, mostly occurs in open character thus becomes necessary to give special attention to the worrying Starter this modality. For this, the work must be induced to maximum attention to the development of physical, always respecting the age of children, and if they are not prepared to receive the teachings of the technical foundations, it is the teacher or coach to develop this work.
Keywords: sporting initiation; physical abilities; basketball; children